2022
DOI: 10.1021/acsami.2c01925
|View full text |Cite
|
Sign up to set email alerts
|

Degradation and Self-Healing in Perovskite Solar Cells

Abstract: Organic−inorganic halide perovskites are well-known for their unique self-healing ability. In the presence of strong external stimuli, such as light, temperature, and moisture, high-energy defects are created which can be healed by removing the perovskite from the degradation source. This self-healing ability has been showcased in devices with recoverable performance and day-and-night cycling operation to dramatically extend the device lifetime and even mechanical durability. However, to date, the mechanistic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 78 publications
0
33
0
Order By: Relevance
“…The organic cation precursor solution with AM1 or AM1+SH solution formed a precipitant on the bottom of the vial within 1 day of storage in the glovebox (Figure A), which is expected to be ammonium chloride resulting from the combined degradation of FAI and MACl (Figure S21). The amount of precipitant is related to the amount of AM1 in the solution (Figure S22). On the contrary, the AM1+SEH solution is stable for more than one month (Figure B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The organic cation precursor solution with AM1 or AM1+SH solution formed a precipitant on the bottom of the vial within 1 day of storage in the glovebox (Figure A), which is expected to be ammonium chloride resulting from the combined degradation of FAI and MACl (Figure S21). The amount of precipitant is related to the amount of AM1 in the solution (Figure S22). On the contrary, the AM1+SEH solution is stable for more than one month (Figure B).…”
Section: Resultsmentioning
confidence: 99%
“…In the sequential deposition process, FAI and MACl dissolved in an isopropanol (IPA) solution must first diffuse into PbI 2 before the thermal annealing. However, the limited solubility of MACl, low boiling point of IPA, and low diffusivity of FAI into PbI 2 grains complicate this conversion process. ,, Ultimately, incomplete conversion results in large domains of PbI 2 , which degrade under continuous illumination into Pb 0 and I 2 , starting the autocatalytic degradation of FAPbI 3 . Therefore, alternative options to control the crystallization of FAPbI 3 are needed.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research revealed that organic–inorganic halide perovskites possess a unique self‐healing ability, that the high‐energy defects can be healed by removing the perovskite from the degradation source. [ 282 ] Such property is favorable to the lifetime under the day‐and‐night cycling operation, especially for flexible devices. The healing mechanism was based on the reversible weak chemical bonds formed in the polymer chains by reversible dynamic non‐covalent bonds, like hydrogen bonds, dynamic metal–ligand interaction, hydrophobic interaction, and dynamic covalent bonds.…”
Section: Mechanical Stabilities Of Fpscsmentioning
confidence: 99%
“…Nevertheless, SHP-based electronics suffer from high fundamental incompatibility at the SHP and the brittle semiconductor interface such as imbalance between crystallinity ratio, chain mobility, high glass transition temperature (T g ), softness, and electron mobility, resulting in high mechanical and electrical failure. [38,39] Therefore, SHP are required to be tough with highly dynamic self-healing function to accommodate conductive component. [40,41] Recently, our group developed an SHP with low T g , entropic-driven self-healing mechanism with high encapsulation power of PNCs for sensing and white LED application with remarkable sustainability.…”
Section: Introductionmentioning
confidence: 99%